Investments in dairy farms enlargement in Serbia: A tool for poverty reduction in rural areas (African Journal of Dairy Farming and Milk Production, 2013)
Production is one of the most important economic activities in Serbian rural areas, which faces significant problems regarding unemployment and poverty. To increase income and employment, family farms have to enlarge dairy operations, modernize production process, buildings and equipment. The goal of this paper is to determine economic effectiveness of investments in two possible dairy farm developing models. It was supposed that farmers invested in enlargement of dairy farms from 30 to 100 cows herd. It was determined that investments in both production types were economically profitable. To determine which production type is more economically acceptable in risky environment, scenario analysis method was used. In risky circumstances, investments in farms specialized in milk production had greater expected net present value and were less risky than investments in combination of milk, heifers and steers production. In the paper, agricultural policy measures necessary to support such family farms developing model were recommended.